مناهج التأليف الأدبي في القرن الثالث الهجري - زردة يوسف; ديوب هيفاء (Latakia University Journal - Arts and Humanities Sciences Series, 2013)
يسلّط البحث الضوء على منهجين رئيسين تتوزّعهما أبرز المؤلّفات الأدبيّة في القرن الثالث الهجري, أوّلهما: منهج الاستطراد القائم على الانتقال العفوي بالقارئ من موضوع إلى آخر, ومن فكرةٍ إلى أخرى من دون رابط منطقيّ, بما في كلّ هذا من إيحاءٍ بالاضطراب , وعدم المنهجيّة , وما يخفي وراءه من دلالاتٍ ونيّاتٍ وآراءٍ قد لا يكون ممكناً التصريح بها , وخير من يمثّل هذا المنهج الجاحظ ت 255هـ الذي يعدّ بحقّ المؤسّس الحقيقي لأسلوب الاستطراد في كتابيه: ( الحيوان , والبيان والتبيين) . وثانيهما: منهج التصنيف والتبويب القائم على ترتيب المفردات المعرفيّة المتجانسة , ووضعها ضمن بابٍ واحد تحت عنوان محدّد, ويعدّ ابن قتيبة ت276هـ في كتابه (عيون الأخبار ) أوّل من شقّ هذا الطريق من خلال تقسيمه كتابه إلى أبواب ينطوي كلّ منها على مجموعة من الأخبار المتجانسة – إلى حدّ ما – لأنّه لا يريد أن يخرج تماماً عن سنّة سار عليها سابقوه وهي الاستطراد, وكان عمله خطوةً رائدة في مجال التصنيف والتبويب, أمّا كتاب (الكامل) للمبرّد ت 285هـ فعلى الرّغم من تقسيمه إلى أبواب إلا أنّه لا يحمل من روح التصنيف شيئاً , وتقسيمه كان شكليّاً فقط . This research highlights two main approaches that are used in the most distinguished literary books in the Hijri third century: The first one is digression. This approach is based on the spontaneous transferring of the readers from a subject or idea to another without a logical connection. This approach may include a hint of confusion and a lack of methodicalness. It may also hide denotations, intentions and viewpoints that could not be made explicit. Al-Jahez (255 Hijri) is the most prominent representative of the approach in his two books (Al-Hayawan) and (Al-Bayan and Altabyeen), Al-Jahez is truly considered the real founder of digression. The second one is the approach of categorization and classification that is based on arranging the cognitive, homogeneous vocabulary and putting them within one chapter with a specific title. In his book (Uyoun Al-akhbar), Ibn Qutaibah is considered the first to begin this method by dividing his book into categories. Each of these categories include a set of partly homogeneous news. This is because he does not want to completely break away from the tradition of digression used by his predecessors. Ibn Qutaibah’s work was a leading stage in the field of categorizing and classification. As for the book (Al–Kamel) by Al–Mubarred; in spite of dividing this book to chapters, it does not hold the essence of categorization, and the division was just formal.